(untitled) (e-Journal of Linguistics, 2023)
The aimed of this research is to examine the part of the particularized conversational implicature and flouting of maxim found in a Netflix movie, named To All the Boys I Loved : Always and Forever. The researcher used the particularized conversational implicature theory by Yule (1996) to identify the utterances and the flouting of maxim by Grice (1976) to categorize the type. The design of this research is descriptive qualitative research. The researcher used the interview method by Sudaryanto to collect data, the pragmatic identity method by Sudaryanto to analyze the data, and used the informal method by Sudaryanto to present the research result. The researcher collected twenty one data that contain particularized conversational implicature, and eight of the data categorized as flouting of maxim quality, four data categorized as flouting of maxim quantity, five data categorized as flouting of maxim relevant and four data categorized as flouting of maxim manner.The result concludes that out of the twenty one analyzed data, flouting of the maxim relevant in the particularized conversational implicature is the most used apply in the movie.